2017
DOI: 10.1115/1.4035957
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Turbulent Flow Around a Square Cylinder With Rounded Corners

Abstract: Predictions are reported of the two-dimensional turbulent flow around a square cylinder with rounded corners at high Reynolds numbers. The effects of rounded corners have proved difficult to predict with conventional turbulence closures, and hence, the adoption in this study of a two-equation closure that has been specifically adapted to account for the interactions between the organized mean-flow motions due to vortex shedding and the random motions due to turbulence. The computations were performed using ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The computational fluid domain is shown in Figure 2a, where its dimensions are given in multiples of D. The inlet, outlet, and side boundaries of the computational domain are located at distances of 10D, 25D, and 10D, respectively, from the cross-section. The dimensions of the fluid domain were chosen so that flow development far from the cross-section was not affected and so that it could be comparable with previous numerical studies [32,33,36]. Initial analyses for varying D values confirmed that the results are independent of D; thus, this problem may be non-dimensionalized.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The computational fluid domain is shown in Figure 2a, where its dimensions are given in multiples of D. The inlet, outlet, and side boundaries of the computational domain are located at distances of 10D, 25D, and 10D, respectively, from the cross-section. The dimensions of the fluid domain were chosen so that flow development far from the cross-section was not affected and so that it could be comparable with previous numerical studies [32,33,36]. Initial analyses for varying D values confirmed that the results are independent of D; thus, this problem may be non-dimensionalized.…”
Section: Computational Modelmentioning
confidence: 99%
“…Zhang et al (2017) [35] performed URANS simulations with Spalart-Allmaras (SA), standard k-ω, and k-ω (SST) turbulence models at Re = 2.2 × 10 4 , but observed that the one-equation Wray-Agarwal (WA) turbulence model agreed more with experimental data. Finally, Dai et al (2017) [36] performed URANS simulations with the modified k-ε turbulence model, and they demonstrated the drag reduction effect of the presence of rounded corners instead of sharp ones in a square cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed modification was subsequently tested in a wide range of flows that are strongly influenced by vortex shedding. These included the benchmark flow around isolated square and circular cylinders (Younis and Przulj, 2006), the flow around a full-scale Tension Leg Platform (Dai et al, 2015), and the flow around a square cylinder with rounded corners (Dai et al, 2017). In each case the results obtained with the modified model were distinctly better than those obtained with the standard formulation.…”
Section: Computational Detailsmentioning
confidence: 99%
“…They further extended their work by studying the shear-inflow effects for the above simulated cases in [23] and [24]. Other numerical studies on rounded corner cylinders are summarised in [25,26].…”
Section: Introductionmentioning
confidence: 97%